Pengaruh Kualitas Pelayanan, Fasilitas, Dan Ketepatan Waktu Delivery Cargo Terhadap Kepuasan Pengguna Jasa Pabean Di PT. Biru Pratama Logistindo Line Semarang - Afifatul Gholimah; Darsono Darsono (Jurnal Ekonomi Manajemen Akuntansi, 2021)
Today's business competition requires companies to be able to compete with other companies. PT. Biru Pratama Logistindo Line is a company engaged in import-export services. This study aims to determine the relationship between service quality, facilities and timeliness of delivery of the satisfaction of service users of PT. Biru Pratama Logistindo Line. The data analysis technique used is multiple linear regression analysis and the sampling technique uses proportional random sampling with 42 respondents as consumers of PT. Biru Pratama Logistindo Line taken from a total population of 62 consumers. The analytical tool used in this research is SPSS (Statitical Package for Social Science) Version 22.0.